Pengaruh Rasio Daging Ayam Broiler (Gallus Domesticus) Dengan Jamur Merang (Vorvariella volvacae) Terhadap Karakteristik Lawar Ayam dan Dampak Terhadap Penurunan kolesterol - Sri Agustini, Ni Ketut; Yusa, Ni Made; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i03.p10, 2022)
This study aims to determine the effect of the ratio of broiler chicken meat to merang mushrooms on the characteristics of chicken lawar, to determine the right comparison between chicken meat and merang mushrooms that can produce chicken lawar with the best characteristics and to determine the effect of adding merang mushrooms on reducing blood cholesterol levels of animals experimental wistar rats. The study is divided into two stages. The first stage of lawar making where meat and merang mushrooms are mixed with a ratio between broiler chicken meat and merang mushrooms 100: 0., 90: 10., 80: 20., 70: 30., 60: 40., and 50: 50 then followed by testing fat content, crude fiber content, and sensory evaluation carried out with a hedonic test (favorability) and scoring test. The second stage is the analysis of total cholesterol which is carried out invivo using the best treatment and chicken lawar with a concentration of P0. This type of research is experimental laboratory using the Control Group Post Test Design research design. The data were analyzed with analysis of variance (ANOVA) and continued with duncan test. The results of the phase I study showed that the ratio of broiler chicken meat to merang mushrooms had a very noticeable effect on moisture content, fat content, crude fiber content, hedonic taste, aroma, texture scoring, overall acceptance. P5 treatment with a broiler chicken meat ratio of 50% and merang mushrooms of 50% is the best treatment. The results of the phase II study showed that in the posttest of feeding treatment, namely standard feed mixed with lawar, had a very noticeable effect on the total blood cholesterol levels of rats, there was a decrease in the total blood cholesterol levels of rats in the K2 group, which was 8%, while in the K1 group there was a slight increase in cholesterol levels by 12% and the K3 group there was an increase in total cholesterol levels which was quite high, namely by 64%.